Dental Caries among the patients visiting HBS Dental College Hospital Islamabad - Sobia Siddique, Abdul Manan Shahid, Hina Mahmood, Naveen Farooq, Sara Ali, Shahida Maqbool (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dental caries is a common, chronic microbial disease affecting the teeth of huge population worldwide. It is a progressive but preventable and treatable disease which has an impact on oral as well as general health of patients. Aim: To assess the frequency and pattern of caries spread in the patients visiting HBS Dental College Hospital Islamabad. Methods: It is a descriptive cross sectional study carried out at HBS Dental College Hospital Islamabad from August 2021 to Jan 2022, to find the frequency and pattern of caries affecting the teeth of patients. It consisted of 840 patients, 522 males and 318 females, examined in oral diagnostic department and assessed by dentition status and treatment need (WHO 1997). Results: Teeth affected with dental caries The results showed 48% incidence of dental caries among the patients examined including 57% males and 43% females, being more in males (p<0.05) and posterior teeth specially 2nd molar compared to other teeth. Conclusion: Health professionals and dentists need to educate people about its risk factors and instruct them proper oral hygiene and brushing techniques. Lack of education and poor quality of life are among the main causes.